THE DUAL INSURANCE MODEL AND ITS IMPLICATIONS FOR INSURANCE DEMAND AND SUPPLY POST-CHRISTCHURCH EARTHQUAKES IN NEW ZEALAND - Mumo, Richard K.; Watt, Richard (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2016)
This paper gives an empirical analysis of the insurance reactions post-Christchurch earthquakes of 2010-2011. In a broad sense, the paper examines the earthquakes’ ramifcation for the supply-side of the entire insurance industry in New Zealand as well as going further to give a narrow analysis of the implications for individual insurance companies. The research has been motivated by the unique attributes of the New Zealand natural disaster insurance scheme. This has helped private insurance companies to provide insurance coverage at competitive premium rates even when the probability of a catastrophic event is considered high in New Zealand. The study starts with a market analysis that points to the need for government intervention in natural disaster insurance provision in countries prone to disasters. The paper illustrates the framework for natural disasters in New Zealand as well as giving supply-side changes that were experienced in the aftermath of Christchurch quakes.